The Increasing Role of Practical Reason in the Human Development Reports - Crespo, Ricardo Fernando (2013)
This paper will argue for the need to reinsert practical reason into economics. It will first define, classify, and characterize practical reason. Second, it will show how it applies to Economics (Section 3). Then, it will note the presence of this use of reason in the construction of the United Nations Development Program's (UNDP) Human Development Index (Section 4). Finally, the paper will maintain that the UNDP is increasingly making use of this form of reason (Section 5).